Design and development of an apparatus for grating and peeling fruits and vegetables - Mustapa Kamal, Siti Mazlina; Abd Rahman, Nur 'Aliaa; H., Nor Hidayati; Mohd Shariff, Intan Shaidatul Shima; Wan Hasan, Wan Zuha (Academic Journals, 2010)
Fruit grater and peeler are needed in the processing of fruits in order to reduce the time required for fruits grating and peeling. Grating is important especially to make salad and for decoration purpose. A suitable grater is needed for specific decoration process. It is crucial for food (processing) industry to operate at minimal operating cost. Peeling using hands is time consuming and may require several workers to perform the operation and thus may increase the operating cost. Therefore in this study, a machine was designed to combine the process of grating and peeling in one device. This new designed machine is suitable to be used domestically. The machine is small-sized and lightweight and is convenient to carry and store. It is comprised of a clamping mechanism, grater, peeling blade, movable arm and also a pair of end-cutting blade. The prototype was tested for automatic grating and peeling process and manual peeling was also performed to peel the skin of selected fruits and vegetable. The prototype was able to grate several fruits and vegetables and also reduce the peeling time by 94% when compared to manual peeling.